2018
DOI: 10.1002/jcb.27688
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐130b increases fibrosis of HMC cells by regulating the TGF‐β1 pathway in diabetic nephropathy

Abstract: Basement membrane thickening, glomerular hypertrophy, and deposition of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Hsa-miR-130b-3p is a well-known marker, studied in cellular and animal models, involved at different level in the progression and maintenance of different kinds of cancer, 75 , 76 but it has also been shown to be involved in chondrogenesis and osteogenesis, 77 associated with obesity, insulin resistance, and other pathophysiological processes. 45 , 78 A previous study has shown how inflammatory signals, such as TNFα and IL-1β, induce its action in adipose inflamed tissue. 44 So far, the presented results show a higher expression of hsa-miR-130b-3p in patients with low chronic postoperative pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-130b-3p is a well-known marker, studied in cellular and animal models, involved at different level in the progression and maintenance of different kinds of cancer, 75 , 76 but it has also been shown to be involved in chondrogenesis and osteogenesis, 77 associated with obesity, insulin resistance, and other pathophysiological processes. 45 , 78 A previous study has shown how inflammatory signals, such as TNFα and IL-1β, induce its action in adipose inflamed tissue. 44 So far, the presented results show a higher expression of hsa-miR-130b-3p in patients with low chronic postoperative pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…After protein quantification via the BCA method, protein samples were mixed with loading buffer and then denatured at 100°C for 5 min. The protein samples were separated by SDS-PAGE as previously described ( 15 ). In brief, equal amount of protein (30–50 μg) were loaded into 8%, 10% or 12% gel for electrophoresis and then transferred onto PVDF membrane (Millipore).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of a currently clinical-trialed DN drug, Atrasentan (an endothelin-1 receptor antagonist) reduced miR-21 expression, restored the Foxo1 expression, and thus promoted renal autophagy (Wang et al, 2019a). Therefore, following TGFB response, majority of these downstream network of miRNA activates the PI3K/AKT/mTOR pathway, by targeting the PTEN (miR-216a, miR-217, miR-21, miR-22, miR-25, and miR-214) (Kato et al, 2009;Denby et al, 2011;Li et al, 2017a;, collagen type I alpha1 (COLIA1), Collagen IV (COL4), and Fibronectin (FN) (miR-130b) (Ma et al, 2019), PI3K inhibitor (Fog2) (miR-200 family) (Park et al, 2013), Tyrosine 3monooxygenase (Ywhab) (miR-451) (Zhang et al, 2012), DEP domain-containing mTOR-interacting protein (Deptor) (miR-181a) (Maity et al, 2018), Protein canopy homolog-1 (Cnpy1) (miR-370) (Yu et al, 2019), high−mobility group AT−hook-2, Hmga2 (let-7a-5p) (Wang et al, 2019c), Insulin receptor substrate-2, IRS2 (miR-141) (Li et al, 2018b), forkhead box proteins, and Foxo1 (miR-382) (Wang et al, 2018c) genes. Some of these miRNAs are found in circulating bio-fluids and therefore, could potentially be as biomarkers.…”
Section: Micrornas In Renal Hypertrophy and Ecm Accumulationmentioning
confidence: 99%